Abortion Under the Malaysian Penal Code: A Comparative Appraisal - Mohamad Yunus, Mohamad Ismail; Mohamad Hanifa, Shamshina (LexisNexis Malaysia Sdn. Bhd., 2017)
The objective of this article is to highlight the issue of abortion under the Malaysian Penal Code, its historical and international contexts. By examining the history of abortion and its evolving legal status around the world and Islamic jurisdiction, it is hoped to shed light on how we arrived at our current situation and how the status of the law on abortion in Malaysia can fits into the global picture. This article looks at the selected countries’ laws and practices and the effect of restrictive and non-restrictive abortion and family planning policies on the number of abortions and the health of women and their families. It is ended by focusing on Malaysia and analyzing the need to have a reform on our law relating to abortion. Looking at abortion throughout time, around the globe and on Islamic law point of views provide an interesting and enlightening dimension on this crucial legal issue.